State of Microbiocenosis and Intestinal Local Immunity in Healthy Infants: Results of a Study - L.V. Kvashnina; I.M. Matviyenko (Zaslavsky O.Yu., 2014)
State of intestinal microbiocenosis is one of the key components of the process of formation of health in children. According to the findings of a survey conducted in IPOG of NAMS of Ukraine, up to 60 % of young children (6 months - 3 years of life) without clinical signs of disease were identified dysbiosis degree 1-2 with the predominant formation of bifido- and lactoflora deficit and with growth of pathogenic flora (pathogenic staphylococci, pathogenic enterobacteria, E.coli with altered enzymatic and hemolytic properties), which potentially leads to the formation of pathological processes and, consequently, diseases. In 30-68 % of children (depending on age) we found associations of pathogenic flora, represented mainly by staphylococcus, Klebsiella and fungi from the genus Candida. Decrease of local intestinal immunity against a background of dysbiosis reduces the resistance of children to viral and bacterial infections as well as the intensity of defense reactions of the organism that can lead to a more severe course of infections and increases the risk of chronic pathology.